2016
DOI: 10.1038/srep31662
|View full text |Cite
|
Sign up to set email alerts
|

Green bean biofortification for Si through soilless cultivation: plant response and Si bioaccessibility in pods

Abstract: Food plants biofortification for micronutrients is a tool for the nutritional value improvement of food. Soilless cultivation systems, with the optimal control of plant nutrition, represent a potential effective technique to increase the beneficial element content in plant tissues. Silicon (Si), which proper intake is recently recommended for its beneficial effects on bone health, presents good absorption in intestinal tract from green bean, a high-value vegetable crop. In this study we aimed to obtain Si biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…At the same time, Swiss chard showed slightly lower bioaccessibility of oxalate. According to previous studies [2][3][4][5] the bioaccessibility of mineral nutrients can be considerably affected by several factors, including mineral type and food matrix composition. At any rate, all the results of the present study suggest that bioaccessibility, defined as the ability of a nutrient to be released into the gastrointestinal tract, can be considered as a useful tool to better estimate real nutrient intake from vegetable products, especially when innovative cultivation protocols are applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, Swiss chard showed slightly lower bioaccessibility of oxalate. According to previous studies [2][3][4][5] the bioaccessibility of mineral nutrients can be considerably affected by several factors, including mineral type and food matrix composition. At any rate, all the results of the present study suggest that bioaccessibility, defined as the ability of a nutrient to be released into the gastrointestinal tract, can be considered as a useful tool to better estimate real nutrient intake from vegetable products, especially when innovative cultivation protocols are applied.…”
Section: Discussionmentioning
confidence: 99%
“…A novel challenge in agriculture is the production of tailored foods, i.e., foods specifically suitable for target groups of people with particular nutritional needs. In fact, in recent years, a number of studies have highlighted the possibility of producing vegetables for specific physiological conditions, such as biofortified vegetables, with the aim of counteracting different nutritional deficits [1][2][3][4][5][6][7][8]. In general, these authors reported evidence on the use of specific growing protocols aimed to increase the content of specific nutrients in plant tissues, such as iodine (I), silicon (Si), calcium (Ca), selenium (Se), zinc (Zn), and iron (Fe).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that increasing the consumption of alcoholic beer should not be considered a sensible way of increasing the dietary intake of Si; however, nonalcoholic beer might be considered [28]. Cereals, such as barley, oats, wheat, and rice bran, as well as rice and some herbaceous plants, account for 30% of dietary silicon intake, followed by fruits (especially apple and banana), vegetables (particularly carrot, potato, green beans), beverages, nuts, and some dried fruits [26,29,30]. Collectively, these foods provide more than 75% of dietary silicon intake [31].…”
Section: Sources and Bioavailability Of Silicon From Foodsmentioning
confidence: 99%
“…Amorphous diatomaceous earth is insoluble in water. However, it is presumed that when silica is hydrated in the body, it is converted to OSA, which is, in turn, soluble in water, increasing its bioavailability and facilitating absorption in the gastrointestinal tract [30]. In the available literature, there is no data on the bioavailability of diatomic organic silicon in amorphous and crystalline forms.…”
Section: Diatomaceous Earth As a Supplementmentioning
confidence: 99%
“…Color measurements were performed using a colorimeter (CR-400, Konica Minolta, Osaka, Japan) equipped with illuminant D65, operating in reflectance mode and with the CIE L (lightness) a * (redness) b * (yellowness) color scale, according to the procedure described by Montesano et al [25]. The colorimeter was preliminary calibrated with a standard reference material characterized by L, a * and b * values of 97.55, 0.52 and 1.45, respectively.…”
Section: Plant Growth and Color Parameters Measurementsmentioning
confidence: 99%